Towards co-constructed coaching: Exploring the integration of coaching and co-constructed autoethnography in leadership development. Issue 4 (September 2013) - Kempster, Steve; Iszatt-White, Marian
This article introduces a new method for leadership development: co-constructed coaching. The terrain of executive coaching is outlined and contrasted with co-constructed coaching that draws on the research method of co-constructed autoethnography. In particular the relative merits of directive versus non-directive leadership development interventions are examined, along with the issue of multiple agendas in coaching/research relationships in this context, and the implications, both positive and negative, of having a highly informed active partner in the leadership learning process. The paper makes a contribution to management learning by presenting co-constructed coaching as a credible and potentially beneficial alternative to executive coaching by enabling a critically reflexive dialogue.